Factors Influencing Employees’ Innovative Self-Efficacy in the High-Tech Industry in China - Liu, Cong (2014)
To response to the turbulent business environment, companies in high-tech industry must innovate to obtain competitive advantages for survive in a long run. Researchers and practitioners suggest that employee innovative work behavior is the key to companies’ continuous innovation. As in China, who is the second largest economy in the world and put lots of effort on her innovation capability, the innovation capability is still limited. Further research has defined the reason for the limited innovation capability in China is the low employee innovation self-efficacy. Within this context, this research devoted to identify factors influencing employee innovative self-efficacy and determine which factors have the strongest influence on their innovative self-efficacy in China. Literature review examines employees’ personal characteristics and contextual factors have positively influences on innovative self-efficacy (ISE). Precisely, it determines the personal characteristics are core self-evaluations (CSE), and three contextual factors are organizational support for innovation (OSI), transformational leadership (TL), and co-worker exchange (CWE) respectively. To achieve the objectives of the research, a quantitative approach was adopted with questionnaire as a tool. SPSS 20.0 was used to do descriptive statistics analysis and frequency analysis. Smart PLS 3.0 was utilized to run reliability, validity as well as hypothesis test in order to examine relationship among constructs. The outcome of the study indicates three out of the four independent variables are significant, which are ESE, OSI and CWE. In contrast with the hypothesis, the relationship between TL and ISE is not significant. Additionally, CWE and OSI have the strongest influence on ISE among employees working in the high-tech industry in China.